Memupuk Jiwa Pustakawan Sejak Dini: Refleksi Implementasi Literasi Informasi dalam Menciptakan Masyarakat Terinformasi - Alam, Umar Falahul (Daluang: Journal of Library and Information Science, 2021)
Introduction. information literacy for all of the community is a condition that is predicted by the Indonesian government to be realized immediately. This achievement will create an informed society. This situation can be realized if the librarian's soul becomes the soul of the community. Therefore, two things that must be prepared are first, increasing interest in reading in the community, and second, carrying out an information literacy program.Methodology. This paper is library research. Writing analysis uses a qualitative descriptive method by capturing the fact. This study uses relevant literature to relate the research theme in formulating the problems that occur and in making final conclusions.Results and discussion. Librarians who are referred to as "guardians of knowledge", have an enlightening spirit compared to other professions. There are two guidelines that can make this enlightening soul, the first is code of ethics, and the second is the activities of the librarian's functional position. These two guidelines provide direction for librarians in carrying out sustainable activities to improve information literacy skills for the community. Many programs have been implemented to develop this information literacy program, by various librarians, but today, informed society has not created the programs yet.Conclusion. So far, this information literacy program has not realized the informed society. Information literacy programs that have been developed must not stop and must be implemented. An informed society will be formed if all levels of society reflect the librarian's spirit in life.